Polissacarídeos de Passiflora edulis fo. flavicarpa O. Deg., Passilfloraceae: estudo químico-estrutural e avaliação dos efeitos antitumoral, antidiabético e anti-inflamatório - Silva, Dráulio Costa da (2011)
Studies indicate that carbohydrates considered dietary fiber protect against cardiovascular diseases, obesity and diabetes. These molecules are considered pharmacologically active since that modify the biological response, including by improving the immune response, being reported by reducing the risk of developing some cancers. Passion fruit (Family Passifloraceae) is a typical plant of tropical and object of several studies in phamiacology. The skin of the imit is rich in carbohydrates sources of fiber, especially pectin. This work purposes to isolate and characterize stmcturally and chemically a polysaccharide fraction from the bark of yellow passion fmit (Passiflora edulis fo. Flavicarpa O. Deg.) and the evaluation of anti-tumor, antidiabetics and anti-inflammatory in animals models [...]